Relações de gênero no cotidiano escolar: concepções, discursos e práticas - Teodoro Junior, José do Carmo [UNESP] (Universidade Estadual Paulista (Unesp), 2010)
Gender‟s concept understands that differences and inequalities established between men and women are historically and culturally constructed. In this way, the meanings and representations of gender are constituted and reconstituted in the social realm through various institutions, practices and relationships presents in a social group. The school as an institution responsible for the formal education of children, youth and adults, produces and reproduce speeches that (re)constitute meanings, identities and representations of gender. Based on this assumption, this research aims at analyzing the routine practices of kindergarten and early elementary school years at a public school in the state of Sao Paulo about gender relations. Therefore, this study aims to broach how discourses and attitudes of teachers, students and other subjects produce and reproduce the representation and gender identities. Form this purpose, the study first presents a literature about the subject to later present the research results obtained through the questionnaire applied with teachers and the daily school practices‟ observe of the school

O conceito de gênero propõe que as diferenças e desigualdades estabelecidas entre homens e mulheres são histórica e culturalmente construídas. Dessa maneira, os significados e representações de gênero são constituídos e reconstituídos no campo do social por meio das variadas instituições, práticas e relações que a constitui. A escola enquanto instituição responsável pela educação formal de crianças, jovens e adultos, produz e reproduz discursos que (re)constituem significados, representações e identidades dos gênero. Partindo desse pressuposto, essa pesquisa tem por objetivo a análise das práticas rotineiras da Educação Infantil e dos anos inicias do Ensino Fundamental de uma escola pública do interior do estado de São Paulo acerca das relações de gênero. Assim, esse estudo visa abordar como os discursos e posicionamentos de professores, alunos e outros sujeitos produzem e reproduzem as representação e identidades de gênero. Para tanto, o estudo primeiramente apresenta um levantamento bibliográfico sobre o tema para, posteriormente, apresentar os resultados da pesquisa obtidos por meio do questionário aplicados aos professores e observação das práticas cotidianas da escola
Keywords: Educação; Relações de gênero; Práticas educativas; Education; Educational practices